2022
DOI: 10.1590/s2175-97902022e181053
|View full text |Cite
|
Sign up to set email alerts
|

The impact of therapeutic hypothermia on peripheral blood cell in newborns with hypoxic ischemic encephalopathy

Abstract: The effect of hypothermia treatment on white blood cell (WBC), neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR) and platelet-to-lymphocyte ratio (PLR) values as an indicator of inflammation was evaluated in newborns with hypoxic ischemic encephalopathy (HIE). The study was performed that the before-therapeutic hypothermia (TH) and after-TH WBC, lymphocytes, neutrophils, monocytes and NLR, LMR and PLR values of the complete blood cell count were retrospectively evaluated. The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Studies in human patients with stroke have shown a high number of peripheral neutrophils being associated with the severity of injury [ 71 ], as well as in neonatal HI associated with poorer neurological outcomes [ 26 ]. It has been shown that TH has a minimal effect on peripheral immune cell counts in neonatal HI cases [ 72 ]; however, HI neonates undergoing TH have altered inflammatory responses compared to healthy infants [ 73 ]. It is commonly believed that an increase in neutrophil count after HIE is possibly associated with an infection and adverse outcome; however, evidence has shown no significant changes in the neutrophil count in asphyxiated newborns [ 27 ], even less during TH [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in human patients with stroke have shown a high number of peripheral neutrophils being associated with the severity of injury [ 71 ], as well as in neonatal HI associated with poorer neurological outcomes [ 26 ]. It has been shown that TH has a minimal effect on peripheral immune cell counts in neonatal HI cases [ 72 ]; however, HI neonates undergoing TH have altered inflammatory responses compared to healthy infants [ 73 ]. It is commonly believed that an increase in neutrophil count after HIE is possibly associated with an infection and adverse outcome; however, evidence has shown no significant changes in the neutrophil count in asphyxiated newborns [ 27 ], even less during TH [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that TH has a minimal effect on peripheral immune cell counts in neonatal HI cases [ 72 ]; however, HI neonates undergoing TH have altered inflammatory responses compared to healthy infants [ 73 ]. It is commonly believed that an increase in neutrophil count after HIE is possibly associated with an infection and adverse outcome; however, evidence has shown no significant changes in the neutrophil count in asphyxiated newborns [ 27 ], even less during TH [ 72 ]. Recently, studies in adult animal models of stroke have demonstrated the critical role of neutrophils in the development of inflammation [ 17 , 18 , 19 , 20 , 57 , 65 ]; however, few studies using neonatal HI models have supported this, and the exact role of neutrophils is poorly understood [ 23 , 65 ].…”
Section: Discussionmentioning
confidence: 99%